A novel model for prediction of burst capacity of corroded pipelines subjected to combined loads of bending moment and axial compression. (April 2022) - Shuai, Yi; Zhang, Xiao; Feng, Can; Han, Junyan; Cheng, Y. Frank
Abstract: Most of the commonly used standards and codes for burst pressure prediction at a corrosion defect of steel pipelines generally just consider internal pressure alone. However, an actual oil/gas pipeline is usally subjected to external loads, such as axial compression/tension and bending moment, which may affect the burst capacity of the pipeline. In this study, a three-dimensional (3D) nonlinear finite element (FE) model validated by burst tests was developed to investigate the effect of bending moment and axial force on the burst capacity of corroded pipelines. Subsequently, the effects of external loads (i.e., bending moment, and axial force) and corrosion geometry features (involving corrosion depth, width, length, and clock position) on the pipe burst pressure were determined. Then, based on a series of FE cases, a new burst prediction model for corroded pipelines subjected to the combination loads of bending load and axial compressive force was fitted and developed. Finally, the effectiveness and reliability of the new proposed model were verified by extensive parametric FE analysis and burst test data. The results show that the prediction errors for the failure pressures between the proposed-model and the FEM were less than 10% for most 92.793% of the 222 cases. Moreover, the proposed model can also be applied to the condition that the pipeline is under single internal pressure, and its prediction accuracy is better than that of other seven well-known models of ASME B31G, Mod B31G (0.85 d L), Z662, DNV, PCORRC, CUP, and Shell-92. Highlights: Developed a finite element model for corrosion defect assessment on pipeline under bending moment and axial force. Determined the effect of corrosion width on failure pressure of pipelines. Considered the effect of clock position of corrosion defect on burst pressure of pipelines. Proposed a novel burst capacity model for corroded pipelines under bending and axial compression loads. Determined the effect of bending moment and axial force on failure pressure of corroded pipelines.